A The Influence of Service Quality and Facilities on Cafe Customer Satisfaction: A Meta Analysis - Agusti Efi; Rendi Rezki (The Indonesian Journal of Computer Science, 2024)
This study analyzes the Influence of Service Quality and Facilities on Customer Satisfaction. The articles used as research samples were published nationally, indexed by Google Scholar, and Sinta. The articles used as samples were published from 2019-2024 with the title Influence of Service Quality and Facilities on Customer Satisfaction. The results of a review of 15 studies showed an influence of service quality and facilities on customer satisfaction with a value of 0.57 (95% CI = 0.371 to 0.991). Research inconsistency shows a high value. High inconsistency in research indicates that the results between studies are inconsistent, possibly due to differences in methodology, samples, or context. This indicates that the relationship between variables is not universal and requires further analysis. Varied correlation results will indicate a high heterogeneity value. High heterogeneity indicates that the research results are inconsistent, with different correlation values.